On a case of sleeping sickness - Odriozola, Ernesto (1920)
In the session of the "National Academy of Medicine" on August 4, of last year, Dr. Carlos Monge, noted one case of encephalitis lethargica observed by him in his private practice, and myself doing the same indication, in a patient of his service "Dos de Mayo" whose history, gathered by our hospital chief Dr. CARLOS BAMBAREN clinic is fairly complete and well documented, so it is worth analyzing and collecting the teachings derived from she. The fact that it is a topical issue and having the said disease made ​​its appearance in the field of nosology, during the last epidemic of grippe, he printed importance and practical interest awakens first order.